Wild Boar-Specific PCR Assay and Sequence Analysis Based on Mitochondrial Cytochrome-B Gene for Halal Authentication Studies - Ganea Qorry Aina; Abdul Rohman; Yuny Erwanto (Universitas Gadjah Mada, 2020)
Wild boar meat (WBM) is non-halal meat widely abused in Indonesia. The most common case is mixing beef with WBM either in raw or processed foods. Therefore, it is necessary to develop a detection method of WBM contamination. The objective of this study was to employ polymerase chain reaction (PCR) and sequence analysis using species specific primer (SSP) targeting on wild boar mitochondrial cytochrome-b (CYTBWB2-wb) gene for the identification of WBM in a meatball. The specificity of primer was tested, and the amplicon size was confirmed with conventional PCR and agarose electrophoresis. The base sequences were analyzed using GeneStudio software and subjected to BLAST using NCBI. CYTBWB2-wb primer was also used to test the reference meatballs made from beef and WBM using real-time PCR. The result showed that CYTBWB2-wb amplified wild boar Cyt-B mt-DNA gene specifically. The amplicon size was 194 base pair (bp) with a similarity of 93–98% toward gen Cyt-B mt-DNA of several wild boar types. The primer is able to detect WBM on the reference meatballs up to 0.1% wt/wt with efficiency value of 108.0% and coefficient of determination (R2) of 0.970. The CYTBWB2-wb primer proved to be specific and could be used as a standard method to identify the presence of WBM contamination in meatball products for halal authentication studies.